Online Shopping Behavior Model: Determining the Factors Affecting Repurchase Intention - Nofrialdi, Reski; Melli Herfina (Journal of Law, Politic and Humanities, 2021)
The growth of digital marketing technology is increasingly being used by e-commerce players in offering each particular product or service. The convenience and perceived benefits in the context of online shopping behavior create new competitors that are increasingly innovative and competitive. This phenomenon is important to study and analyze the dominant factors in influencing repurchase intention, because e-commerce players make repurchase intention factor a determining factor in business continuity. The results of the study and analysis of various relevant literature, the researcher proposes a model that can be used as a reference to build an empirical model, namely repurchase intention built by e-risk, e-trust, and rating review.